Sistemas lineares: Abordagem por situações-problema - Ferreira Júnior, Adilson Reis (2024)
This work deals with Linear systems: Resolution and applications in high school. Initially, we dedicate our attention to the theory of linear systems and their resolution. We focus on a specific resolution method: Row reduction. In a second part of the work, we present a geometric interpretation for linear systems of two equations and two unknowns with the help of the GeoGebra software. Finally, the most important part of this work, which is the presentation of linear systems through problems. I used some problem situations to be interpreted and modeled using linear systems, problems that ranged from basic to advanced in terms of modeling and resolution difficulty. This concludes my work having presented the key concepts regarding the modeling, resolution and discussion of a linear system.